RELIGION, MODERNIZATION AND THE ISLAMIC UMMAH - Hassan, Riaz (Journal of Al-Tamaddun, 2018)
In this paper I explore the impact of modernization and social change on the Islamic ummah (community of believers) and how they are shaping the emerging struggle between ‘hybridity’ and ‘authenticity’ among Muslims and Islamic movements. The paper will explore the challenges of this struggle and its sociological implications for the ‘de-centering’ of the Muslim world into multiple autonomous regions. I argue that the future of the Muslim ummah may gain strength not as a unified and unitary community, but as a differentiated community consisting of ummahs representing different Islamic regions. Each regional ummah will possess and embody a unique character that has been moulded by the history and temperament of its people. The paper will conclude with some observations on the future religious, intellectual, economic and political trajectories of Muslim countries.